Metastasis of Rectal Signet Ring Cell Carcinoma to Typical Lipoma: A Rare Presentation of the Tumor-to-Tumor Metastasis Phenomenon - Houyem Mansouri MD; Ines Zemni MD; Nedia Boujelbene MD; Fatma Saadallah MD; Mohamed Ali Ayadi MD; Leila Achouri MD (SAGE Publishing, 2024)
Rectal signet ring cell carcinoma represents a rare subtype of colorectal adenocarcinoma known for its aggressive biological nature and poor prognosis. Although the co-occurrence of colorectal carcinoma with other tumors has been reported, the uncommon phenomenon of tumor-to-tumor metastasis, first described in 1930, remains rare. The most frequent donor neoplasms are lung or breast carcinomas, whereas cerebral meningiomas have been reported to be the most frequent recipient neoplasms. Here we report a case of a typical lipomatous tumor harboring metastatic signet ring cell rectal carcinoma. It is about a 42-year-old man diagnosed with rectal signet ring cell carcinoma and treated with concurrent radiotherapy and chemotherapy followed by an anterior resection and manual coloanal anastomosis with a temporary ileostomy. During the surgery, an abdominal wall lipoma was discovered and excised. A histopathological examination revealed infiltration of the fibro adipose tissue by a mucinous adenocarcinoma with a contingent of signet ring cells. The patient died 12 months after adjuvant chemotherapy due to peritoneal progression. To the best of our understanding, this represents the initial documented instance of tumor-to-tumor metastasis from rectal signet cell carcinoma to a conventional nonvascular lipoma. Consequently, even if one of these tumors appears clinically and radiologically benign, it is prudent to entertain the prospect of tumor-to-tumor metastasis. Thus, a comprehensive pathologic study of both tumors is highly recommended.